Professional practice Alto Tebujo School - Rodríguez A., Domitilo; Vargas, Víctor (David, Panamá : UDELAS, 2011)
Taking into account the new ways of achieving a Bachelor degree, the professional practice becomes the best option, since it puts into practice the theoretical knowledge in a educational center.
INDEX Thought Dedication Acnowledgement Index Introduction Chapter 1. Professional practice report Chapter 2. Teacher intervention in educational practice 2.1. Framework of reference 2.1.1. Definition 2.2. Assigned department area 2.2.1. Functions and duties Chapter 3. Analysis of the professional practice Chapter 4. Proposal Conclusion Recomendation Reference Annexes
Incluye Index
Documento presentado para optar por el título de Licenciatura en Docencia en Ingles
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- INFORME DE PRÁCTICA DE LICENCIATURA -- TEACHING; FACULTAD DE EDUCACIÓN ESPECIAL; LICENCIATURA EN DOCENCIA EN INGLÉS; ALTO TEBUJO SCHOOL